2016
DOI: 10.18326/ijtihad.v15i1.61-82
|View full text |Cite
|
Sign up to set email alerts
|

In search of peace: Ahmadi women’s experiences in conflict transformation

Abstract: In the last few years, religious conflicts involving a minority Muslim group, Ahmadiyya, have risen dramatically in Indonesia; the most recent being the attack on the Ahmadiyya community in Cikeusik Banten, West Java, where three Ahmadis were killed and the sealing of Al Mishbah Mosque by local government of Bekasi West Java. Understanding the context of violent conflict and the ways individual Ahmadi women take agency to challenge such oppression is an important first step in creating a more equitable and pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Through her research with Ahmadi women in Southern California, Ahmed-Ghosh (2004, p. 77) found that complacency with gender hierarchies in belief systems "may provide the emotional, spiritual and material sustenance that these women are seeking in their attempt to cope with alienation in North America". For many Ahmadi women, who are doubly persecuted (Noor 2015;Sultana et al 2015) as targets of systemic heteropatriarchal and religious discrimination, "their religious affiliation is their only recourse and resort in times of need" (Ahmed-Ghosh 2004, p. 88). Paradoxically, the proclamation that Ahmadi Muslims are not Muslim has led to a community-wide loyalty and devotion in the diaspora rooted in unity, support, and sisterhood.…”
Section: Woman In a Heteropatriarchal Societymentioning
confidence: 99%
See 1 more Smart Citation
“…Through her research with Ahmadi women in Southern California, Ahmed-Ghosh (2004, p. 77) found that complacency with gender hierarchies in belief systems "may provide the emotional, spiritual and material sustenance that these women are seeking in their attempt to cope with alienation in North America". For many Ahmadi women, who are doubly persecuted (Noor 2015;Sultana et al 2015) as targets of systemic heteropatriarchal and religious discrimination, "their religious affiliation is their only recourse and resort in times of need" (Ahmed-Ghosh 2004, p. 88). Paradoxically, the proclamation that Ahmadi Muslims are not Muslim has led to a community-wide loyalty and devotion in the diaspora rooted in unity, support, and sisterhood.…”
Section: Woman In a Heteropatriarchal Societymentioning
confidence: 99%
“…It is a South Asian sentiment rooted in pre-Partition India and spread to proximal countries such as Bangladesh, India, and Malaysia. The state-led persecution of Ahmadis in Indonesia is particularly distressing (Marshall 2018) although notably countered through Indonesian Ahmadi women's activism (Inasshabihah 2020;Noor 2015).…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Under the administration of President Yudhoyono, there were many civil rights violations against Ahmadiyya adherents, including withholding the issuance of identity cards (Kartu Tanda Penduduk/KTP) (Pamungkas 2018) and Family Cards (Kartu Keluarga/KK) (Almujaddidy 2017), marriage registration, and birth certificates (Hicks 2014). Stakeholders have sought reconciliation to overcome the violence and conflicts involving Ahmadiyya adherents in Manislor and build peace among the communities (Noor et al 2016). However, to be impactful, peace initiatives must be part of a perpetual process that builds supportive social systems (Nurdin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…have highlighted the problems of AM women, and there is hardly any such study in the Pakistani context. Men and women can have different perspectives on issues faced by religious minorities, but women's perspectives have been rarely investigated(Noor et al 2015). Furthermore, no study was found which examined the intersectionality of poverty and religious persecution of Ahmadi women.…”
mentioning
confidence: 99%